Design Approach Of Ar Projection Mapping Onto Physical Sculpture - Auzani Zeda, Mohamed Kassim; Hasnizam, Abdul Wahid (Universiti Teknologi MARA, Malaysia, 2019)
This paper visualizes method and processes of a projection mapping exhibition based ceramic sculpture installation entitle Forgotten Forest at the Old Court House from July 6 until July 15, 2018. The installation was presented during the Rainforest Fringe Festival 2018 in Kuching, Sarawak. The study aimed to develop a method to exhibit animation in an art installation form within a given gallery space. Forgotten Forest involved the creation of ceramic sculpture, digitisation of the sculpture model using 3D software and animation production in a form of a projection mapping